1996
DOI: 10.1007/bf00019104
|View full text |Cite
|
Sign up to set email alerts
|

RNA expression patterns of a type 2 metallothionein-like gene from rice

Abstract: A type 2 metallothionein-like gene from rice, OsMT-2 (Oryza sativa metallothionein-like gene-2), was isolated in its cDNA form and sequenced. By northern analyses OsMT-2 expression was shown to be induced under stress by sucrose starvation, heat shock and, to a lesser extent, abscisic acid, but not excess metals, including copper. Its response to sucrose starvation was transient and different from OsMT-1, a type 1 metallothionein-like gene of rice inducible by copper. These results suggest that while OsMT-2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 29 publications
(39 reference statements)
0
37
1
Order By: Relevance
“…Type 3 MTs are expressed abundantly in the ripe fruits (Clendennen & May, 1997;Ledger & Gardner, 1994;Reid & Ross, 1997), and expression of Type 4 MTs, also known as the Ec type, was only found in developing seeds so far (Chyan et al, 2005;Lane et al, 1987). A vast number of stimuli have been demonstrated capable of inducing MT genes expression in plants, including natural senescence (Bhalerao et al, 2003), hormones like ABA (Reynolds & Crawford, 1996), ethylene (Coupe et al, 1995), wounding and virus infection (Choi et al, 1996), heat shock (Hsieh et al, 1995), sucrose starvation (Hsieh et al, 1996), UV-light (Foley & Singh, 1994), cold and salt stress (Reid & Ross, 1997), etc. Apparently, different types of MTs respond to different factors, which is especially true when treated with heavy metal stress under different concentrations.…”
Section: Metallothionein: Metal-binding Protein and Morementioning
confidence: 99%
“…Type 3 MTs are expressed abundantly in the ripe fruits (Clendennen & May, 1997;Ledger & Gardner, 1994;Reid & Ross, 1997), and expression of Type 4 MTs, also known as the Ec type, was only found in developing seeds so far (Chyan et al, 2005;Lane et al, 1987). A vast number of stimuli have been demonstrated capable of inducing MT genes expression in plants, including natural senescence (Bhalerao et al, 2003), hormones like ABA (Reynolds & Crawford, 1996), ethylene (Coupe et al, 1995), wounding and virus infection (Choi et al, 1996), heat shock (Hsieh et al, 1995), sucrose starvation (Hsieh et al, 1996), UV-light (Foley & Singh, 1994), cold and salt stress (Reid & Ross, 1997), etc. Apparently, different types of MTs respond to different factors, which is especially true when treated with heavy metal stress under different concentrations.…”
Section: Metallothionein: Metal-binding Protein and Morementioning
confidence: 99%
“…In angiosperms, MTs can be classified into four types based on the conserved positions of Cys residues (Cobbett and Goldsbrough, 2002). There are some general trends in the expression of these four types of MTs, with type-1 MTs expressed predominantly in roots, type-2 MTs in leaves, type-3 MTs in fruits, and type-4 MTs in seeds (Zhou and Goldsbrough, 1994;Hsieh et al, 1995;Zhou and Goldsbrough, 1995;Hsieh et al, 1996;Guo et al, 2003). We have previously shown that the genome of Arabidopsis contains seven genes encoding MTs (Cobbett and Goldsbrough, 2002).…”
mentioning
confidence: 99%
“…In addition, type 2 MT transcripts preferentially accumulate in aerial tissues, especially leaves, as in soybean MT [27], rice OsMT-2 [9] and LeMTA, LeMTB from tomato [32]. In Vicia faba, Foley and Singh [8] demonstrated through Northern blot analysis that type 2 MT was expressed abundantly in leaves, stems and flowers, and at a low level in roots, but was absent in mesophyll protoplasts.…”
Section: 11mentioning
confidence: 99%
“…For example, the MT in tobacco was strongly induced by tobacco mosaic virus and wounding [7]; and the expression of MT in Vicia faba was reduced when plants were treated with salt, cold, salicylic acid or UV-light [8]. Furthermore, transcripts of OsMT -2 in rice could be induced by sucrose starvation, heat shock and abscisic acid [9]; and the expression of walil in wheat was increased by low-nutrient conditions and wounding [10].…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation